Analisis deteksi logam berat (Pb) pada sampel pangan segar asal tumbuhan (PSAT) menggunakan metode GFA AAS - Wahab, Andi Rizki Berliana Zahra; Makmur, Kurnia; Fakhruddin, Andi (Filogeni: Jurnal Mahasiswa Biologi, 2022)
Heavy metals are natural components found in the earth's crust and are difficult to degrade and are hazardous substances. Lead (Pb) is one of the toxic heavy metals that has the potential to trigger poisoning or even in a long time will cause death, because it can damage tissues in the body of living things. One of the ways to deal with food sources in lead contamination is heavy metal detection analysis using the GFA AAS method. The purpose of this study was to determine the principles and procedures for the detection of heavy metal Pb in PSAT samples using the GFA AAS method at the Makassar Agricultural Quarantine Center. In this study, three samples of PSAT were imported from three different countries, including garlic from China, porang from Malaysia and wheat from Pakistan. Based on the results of research that has been carried out, it is known that the analysis of heavy metal detection of Pb from the three PSAT samples was not detected and was below the threshold set by BPOM so that the three samples were declared not to contain heavy metal lead (Pb).